2015
DOI: 10.1142/s0218625x15500274
|View full text |Cite
|
Sign up to set email alerts
|

ANNEALING TIME EFFECT ON NANOSTRUCTURED n-ZnO/p-Si HETEROJUNCTION PHOTODETECTOR PERFORMANCE

Abstract: In this work, n-ZnO/p-Si heterojunction photodetectors were prepared by drop casting of ZnO nanoparticles (NPs) on single crystal p-type silicon substrates, followed by (15-60) min; stepannealing at 600 C. Structural, electrical, and optical properties of the ZnO NPs¯lms deposited on quartz substrates were studied as a function of annealing time. X-ray di®raction studies showed a polycrystalline, hexagonal wurtizte nanostructured ZnO with preferential orientation along the (100) plane. Atomic force microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The effect of annealing duration on the ideality factor calculated forward bias I-V characteristic was observed is in the range of those reported for ITO/ poly(3,4,ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS)/poly(2-methoxy-5-(2-ethlhexyloxy))-1,4-phenylenevinylene)(MEH-PPV)/Alq3/Lif/Au Schottky diode [24], and comparable to that those reported for ITO/MEH-PPV/A21 [28]. Large values of ideality factor were obtained due to the presence of recombination in the junction deposition or at junction interface [25], besides some structural defects and lattice mismatch between ZnO and CuGaO2 [19]. The improvement of the device performance is attributed to the smoother surface [26].…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…The effect of annealing duration on the ideality factor calculated forward bias I-V characteristic was observed is in the range of those reported for ITO/ poly(3,4,ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS)/poly(2-methoxy-5-(2-ethlhexyloxy))-1,4-phenylenevinylene)(MEH-PPV)/Alq3/Lif/Au Schottky diode [24], and comparable to that those reported for ITO/MEH-PPV/A21 [28]. Large values of ideality factor were obtained due to the presence of recombination in the junction deposition or at junction interface [25], besides some structural defects and lattice mismatch between ZnO and CuGaO2 [19]. The improvement of the device performance is attributed to the smoother surface [26].…”
Section: Methodssupporting
confidence: 74%
“…An obvious increment in the intensity of ZnO (002) peak noticed from 10, 20 and 30 minutes annealing duration indicating better crystallinity. An increase in the diffraction intensity observed with long annealing duration due to the enhanced films quality [19]. However, the intensity of ZnO (002) peak drops at 40 minutes and continues to decrease in longer annealing duration of 60 minutes indicate the films crystallinity deteriorates.…”
Section: Methodsmentioning
confidence: 98%
“…[26]. Higher annealing temperatures improve the grain growth, which may also increase the porosity of the films [27]. Although the RMS values are higher than an ideal smooth surface (a few angstroms), they are still in a comparable range for ZnO-based devices used in various applications [2,28,29].…”
Section: Resultsmentioning
confidence: 99%
“…The threshold voltage approaches 0 V and the reverse bias current increases after 350 • C annealing. It has been reported that mobility increases with increasing grain size [27], and the presence of localized defect sites may act as a leak path. Hence, the rise in the reverse current (dark current) is associated with the crystallization of the ZnO layer.…”
Section: Resultsmentioning
confidence: 99%
“…Great unremtiting efforts have been made by the researches to synthesized ZnO thin films and nanosrtucture ZnO thin films [1][2][3][4][5][6]Zinc oxide (ZnO) is a wide band gap direct semiconductor having a band gap of (3.37) eV at room temperature. It also possesses large exciton-binding energy of 60 meV.…”
Section: Introductionmentioning
confidence: 99%